Recognizing Indigenous Legal Standing in Forest Administration: Advancing Sustainable Management of Customary Forests in Indonesia - Annisa Indah Nuari (Rule of Law Studies Journal, 2025)
Background: Although the Constitutional Court of Indonesia ruled in Decision No. 35/PUU-X/2012 that customary forests are no longer categorized as state forests, the absence of a specific law recognizing indigenous legal status continues to create legal ambiguity. This regulatory gap weakens the legal protection of indigenous peoples and affects the sustainability of forest management practices rooted in traditional knowledge and land stewardship. Aims: This study seeks to explore two key objectives: first, to evaluate the necessity of passing the Indigenous Peoples Bill as a legislative instrument to secure indigenous forest rights; second, to investigate the significance of indigenous community engagement in promoting long-term, sustainable management of customary forests. Methods: Using a doctrinal legal research approach, the study is guided by the sociological jurisprudence framework and Arnstein’s Ladder of Citizen Participation theory. The analysis incorporates qualitative case references from multiple regions across Indonesia, including Java, Kalimantan, Sumatra, Sulawesi, and Papua, offering a diverse perspective on customary forest governance. Result: The research highlights ongoing inconsistencies in the legal framework that restrict indigenous authority over ancestral forests. In many regions, participation by indigenous communities remains limited to consultative levels, failing to reach the stages of power-sharing or partnership. Regions with greater community involvement tend to exhibit stronger outcomes in forest preservation and ecological balance. Conclusion: There is an urgent need for formal legal recognition of indigenous peoples through the ratification of the Indigenous Peoples Bill. Strengthening indigenous participation and legal empowerment is essential to ensuring justice, environmental resilience, and the harmonization of customary practices with national forest governance policies.